Elucidating the microstructure of tungsten composite materials produced by powder injection molding. (August 2020) - Duerrschnabel, Michael; Antusch, Steffen; Holtermann, Birger; Jaentsch, Ute; Baumgaertner, Siegfried; Bonnekoh, Carsten; Hoffmann, Mirjam; Hoffmann, Jan; Rieth, Michael
Highlights: Powder injection molding of five tungsten composite materials. Microstructural characterization via scanning and transmission electron microscopy. Y2 O3 precipitates are the best performing grain stabilizers. Formation of mixed (Ti, W)C with a fcc lattice after sintering. Abstract: A detailed microstructural analysis is one key factor for establishing structure–property relationships, which themselves are essential for manufacturing any device or part thereof. In particular, this paper focuses on the microstructural analysis of tungsten composite materials produced by powder injection molding (PIM). Our combined scanning electron microscopy (SEM) and transmission electron microscopy (TEM) approach revealed that W/TiC and W/Y2 O3 composites are promising candidates for e.g. plasma facing components in future fusion reactors. The grains size distribution of all present phases was a log-normal one. TiC and Y2 O3 precipitates in contrast to HfC ones limited the grain growth of the tungsten matrix during sintering about three times more efficient. The precipitate grain size was for all samples in the range of 1.7 µm–3.5 µm. Chemical interaction was only observed for TiC-based composites in the form of W diffusion into the TiC precipitate forming a mixed (Ti, W) carbide retaining the face-centered cubic (fcc) based crystal structure of pure TiC. The tungsten content in Y2 O3 and HfC precipitates was found to be negligible. La2 O3 was only observed in TEM attached to (Ti, W)C particles in the form of about 100 nm sized precipitates. As result, the Y2 O3 and TiC containing samples are considered as promising materials for further detailed mechanical and microstructural investigations.